PENGARUH LITERASI DIGITAL TERHADAP EFEKTIVITAS PEMBELAJARAN MAHASISWA ADMINISTRASI PENDIDIKAN UNIVERSITAS NEGERI PADANG - Syerli Nitami; Hade Afriansyah; Jasrial Jasrial; Novriyanti Achyar (STKIP Pesisir Selatan, 2026)
Objective: One of the problems with the effectiveness of student learning is the suboptimal critical use of digital information, so strengthening digital literacy is needed to support more effective learning. This study aims to determine the effect of digital literacy on the effectiveness of learning of Educational Administration students at Padang State University. The method used is quantitative with a correlational approach. The study population was 621 students, with a sample of 89 people selected using Simple Random Sampling. Data were collected through a Likert scale questionnaire and analyzed with descriptive statistics including validity tests, normality reliability, simple linear regression tests, t-tests, and coefficients of determination (R2). Results: The results showed that digital literacy was in the good category (mean TCR = 85.14), with the highest score in digital security and ethics (87.05) and the lowest in digital content creation (83.55). Learning effectiveness was in the